TOLERANCE IN MADRASAH STUDENTS BASED ON RELIGIOUS ORGANIZATION AFFILIATES - Septian, Muhammad Rezza; Budiman, Arip (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2021)
This article attempted to depict tolerance among public Islamic senior high school (Madrasah Aliyah Negeri/MAN) students. To this end, a descriptive method with a quantitative approach was applied. As tolerance serves as a key to peaceful life, Islamic senior high schools are expected to enrich the community with tolerant and inclusive Islamic teachings. One of the student development activities in MA is carried out based on their religious organizations, namely Nahdlatul Ulama (NU) and Muhammadiyah. The data were collected using tolerance instruments. The obtained data were analyzed using the paired t-test to determine the difference in students from two different organizations. The participants were MA students who were affiliated with NU and Muhammadiyah. The study found that the students tolerance was categorized as high. This study also found some aspects of tolerance, including equality, respecting diversity, and peace. However, the t-test result indicated no significant difference in tolerance level among students affiliated with NU and Muhammadiyah. The result of this study could be used as a consideration in developing peace and multicultural guidance and counseling programs in Islamic school settings.